2018
DOI: 10.1002/2017gl076592
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water Storage in Marine Sediment on Sea‐Level Change

Abstract: Sea‐level changes are of wide interest because they provide information about Earth's internal structure and the sensitivity of ice sheets to climate change. Here we illustrate the sensitivity of sea level to marine sedimentary water storage by modeling sea‐level responses to a synthetic global sediment redistribution history in which rates and patterns of erosion and deposition are similar to those at present and steady in time from the Last Interglacial to present. Our simulations show that if sediment redis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…Sediment loading is one such process potentially contaminating the sea level record. While regional studies have shown sediment can influence sea level on glacial timescales (Simms et al 2007(Simms et al , 2013Wolstencroft et al 2014;Ferrier et al 2015Ferrier et al , 2018Pico et al 2016), in this paper we pose the question globally: to what extent might sediment loading control the variability of LIG sea level observations, and where are these effects most substantial?…”
Section: Introductionmentioning
confidence: 93%
“…Sediment loading is one such process potentially contaminating the sea level record. While regional studies have shown sediment can influence sea level on glacial timescales (Simms et al 2007(Simms et al , 2013Wolstencroft et al 2014;Ferrier et al 2015Ferrier et al , 2018Pico et al 2016), in this paper we pose the question globally: to what extent might sediment loading control the variability of LIG sea level observations, and where are these effects most substantial?…”
Section: Introductionmentioning
confidence: 93%
“…For depositional areas, we follow Ferrier et al (2017Ferrier et al ( , 2018 in computing the rate of change of sediment thickness as the difference between the rates of deposition and compaction, with sediment deposited at an initial porosity of 0.6 and compacting at a rate given by Equation 2.…”
Section: Sediment Redistribution Historymentioning
confidence: 99%
“…Here f(z) is the porosity at depth z below the sediment surface, fmin is the minimum porosity in fully compacted sediment, k is a compaction coefficient, and sd(z) is the difference between lithostatic and hydrostatic stress at depth z, which depends on the sediment grain density rs and water density rw. Following Ferrier et al (2017Ferrier et al ( , 2018, we adopt values of rs = 2700 kg m -3 , rw = 1000 kg m -3 , fmin = 0.2, and k = 10 -17 Pa -1 s -1 . This approach yields vertical profiles of sediment density and porosity that vary over time, which we use to compute time series of mean sediment column density ̅ !…”
Section: Sediment Redistribution Historymentioning
confidence: 99%
See 1 more Smart Citation